Effect of protein concentration in supplements and frequency of supplementation on the performance of beef cows grazing dormant bluestem range - Beaty, J.L.; Cochran, R.C.; Vanzant, E.S.; Morrill, J.L.; Brandt, Robert T., Jr.; Johnson, D.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty-eight, pregnant, Angus × Hereford cows were used to determine whether response to altering frequency of winter range supplementation depends on the protein concentration in the supplements. Supplements containing 12%, 21%, 31%, or 41% crude protein (CP) were fed either daily (7X) or three times weekly (3X). Both groups consumed 31 lbs of supplement per head weekly. Frequency of supplementation exerted only minor influences on cow performance and had no effect on calf performance. However, cows lost less body weight and condition as CP concentration in the supplement increased. In addition, calf weaning weights were improved with increasing CP in the supplement. In conclusion, the impact of supplement CP concentration was much greater than the impact of alteration in supplementation frequency.
Keywords: Beef; Beef cows; Winter range; Frequency; Protein; Supplementation